Shop drawing of SF11-SF12 Basement-1 (RFA-029_Rev A) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.